2021
DOI: 10.21608/sjfop.2021.249390
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Potassium Silicate and Salicylic Acid on Growth, Flowering and Quality Characters of Dendranthema Grandiflorum Plants Under Greenhouse Conditions

Abstract: The impacts of foliar spraying with different potassium silicate concentrations (0.0, 300, 600 and 900 ppm) and salicylic acid (0.0, 100, 200 and 300 ppm) on growth, flowering aspects and some chemical constituents of Dendranthema grandiflorum (Ramat.) Kitamura plant cv. White Rivor were evaluated. Under plastic house conditions, this experiment was carried out at Ornamental Nursery of Faculty of Agriculture, Zagazig University, Egypt, during the consecutive summer seasons of 2019 and 2020. The treatments were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…The obtained results are consistent with those that have been reported by (Abdelsadek et al 2021) on Dendranthema grandiflorum (Ramat.) Fresh and dry weight (g/plant):…”
Section: Number Of Flower/plantsupporting
confidence: 93%
“…The obtained results are consistent with those that have been reported by (Abdelsadek et al 2021) on Dendranthema grandiflorum (Ramat.) Fresh and dry weight (g/plant):…”
Section: Number Of Flower/plantsupporting
confidence: 93%
“…Among these studies, Hasanv and Nejad (2016) found that weekly application of K2SiO3 at 1 mM significantly improved growth, physiological, and biochemical characteristics of geranium under salinity stress. Similarly, Abdelsadek et al (2021) reported that plant height, number of branches and leaves, root length and total fresh and dry weight of Dendranthema grandiflorum cv. White Rivor is greatly increased as a result of the application of K2SiO3 at 900 ppm.…”
Section: Discussion Discussion Discussionmentioning
confidence: 86%
“…In addition, Farahani et al, 2020 showed that foliar spraying of Si (0.2%) improved the essential oil composition of Damask rose under water-deficient conditions. Similarly, Abdelsadek et al (2021) found that spraying Dendranthema grandiflorum cv. White Rivor with potassium silicate (900 ppm) significantly increased total carbohydrates and total chlorophyll in leaves.…”
Section: Discussion Discussion Discussionmentioning
confidence: 90%
See 1 more Smart Citation